2019
DOI: 10.1007/s13163-019-00336-9
|View full text |Cite
|
Sign up to set email alerts
|

Dunford–Pettis type properties and the Grothendieck property for function spaces

Abstract: For a Tychonoff space X, let C k (X) and Cp(X) be the spaces of real-valued continuous functions C(X) on X endowed with the compact-open topology and the pointwise topology, respectively. If X is compact, the classic result of A. Grothendieck states that C k (X) has the Dunford-Pettis property and the sequential Dunford-Pettis property. We extend Grothendieck's result by showing that C k (X) has both the Dunford-Pettis property and the sequential Dunford-Pettis property if X satisfies one of the following cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
(121 reference statements)
0
16
0
Order By: Relevance
“…In the literature concerning Fréchet spaces, the Grothendieck property is often considered in tandem with the Dunford-Pettis property; spaces satisfying both properties are termed GDP spaces. Their systematic treatment may be found, e.g., in [2,3,16]; for non-Fréchet spaces see, e.g., [56].…”
Section: Ultrapowers and Ultraproductsmentioning
confidence: 99%
“…In the literature concerning Fréchet spaces, the Grothendieck property is often considered in tandem with the Dunford-Pettis property; spaces satisfying both properties are termed GDP spaces. Their systematic treatment may be found, e.g., in [2,3,16]; for non-Fréchet spaces see, e.g., [56].…”
Section: Ultrapowers and Ultraproductsmentioning
confidence: 99%
“…Recall that an lcs E is said to have the Grothendieck property if every weak- * convergent sequence in the strong dual E ′ β is weakly convergent. We proved in [15] that C p (X) has the Grothendieck property if and only if every functionally bounded subset of X is finite, and if X is a sequential space, then C k (X) has the Grothendieck property if and only if X is discrete.…”
Section: Introductionmentioning
confidence: 99%
“…Following Grothendieck [18], an lcs E is said to have the Dunford-Pettis property ((DP ) property for short) if every continuous linear operator T from E into a quasi-complete locally convex space F , which transforms bounded sets of E into relatively weakly compact subsets of F , also transforms absolutely convex weakly compact subsets of E into relatively compact subsets of F . In [15], we proved that C p (X) has the (DP ) property for every Tychonoff space X and showed that C k (X) has the (DP ) property if X is hemicompact or a cosmic space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations